Socio-Economic Burden of Hemodialysis on Patients’ Families - Awais Ahmed, Fajer Alhamdan, Almas Ashraf, Fahad Ali Mangrio, Samiullah Shaikh, Asghar Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic kidney disease has become a global public health issue with extreme incidence in Asian countries, and its burden is growing rapidly throughout the world. Haemodialysis has an adverse effect on the dimensions of many patients. The aim of the study was to determine the overall socio-economic burden of haemodialysis on the patient's families and to identify the main factors that are responsible for the socioeconomic burden of haemodialysis on patient families. Material and Methods: This was an observational, cross-sectional study conducted for three months after approval of ERC, LUMHS at Hyderabad and Jamshoro LUMHS public hemodialysis units. The data were collected by using Questionnaire and a patient's family interview after written consent. The questionnaire consists of demographic variables and variables related to the socio-economic burden on families. Results: Of the 350 subjects, 321 (92%) were males and 29 (8%) were females, with the mean age of 43.47 years with standard deviation 12.924. 51% of the subject had monthly income ranging from 11000 to 20000, while 41% had between 21000 and 50000. Seventy percent of the patients were found to have more than 10 family members. Based on their occupation Shopkeepers 22.3%, Farmers 11.7%, Labors 10.6%, Teachers 9.7%, Drivers 7.1%, students 8.9% and 7.7% were Clerks. Practical Implication: The importance of the research has made it possible to identify how the family caregiver can cope with situations that limit their physical and psychological capacity; it has also been important because the results obtained have served as support for changes in the care provided by nurses working in hemodialysis clinics, integrating the family caregiver as one of their priorities Conclusion: The inevitable stresses and subjective burdens on informal dialysis patients must be recognized and addressed. Care can create huge burdens for caregivers and reduce their physical and psychological health. In order to reduce this burden, various strategies needed to be considered including improving the quality of life of patients, caregiver assessments, coping strategy and addressing interpersonal issues. Keywords: Socioeconomic, hemodialysis, chronic kidney disease, patients’ families, Pakistan, stress.